1996
DOI: 10.1002/hep.510230649
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of platelet-activating factor in cytokine production and neutrophil activation after hepatic ischemia-reperfusion

Abstract: Although platelet-activating factor (PAF) is impli-the basis of hepatic IR injury. Recent studies in this cated as an important mediator in the pathogenesis of field have focused on the involvement of inflammatory hepatic ischemia-reperfusion (IR) injury, the precise cytokines and neutrophils. [1][2][3][4][5][6] Tumor necrosis factor a mechanism of its action has not been studied. We exam-(TNF-a) is reported to have a pivotal role in the cytoined the hypothesis that PAF may influence neutrophils kine cascade a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 41 publications
(11 reference statements)
0
26
0
Order By: Relevance
“…Previous studies have identified a number of key factors associated with liver IR injury, such as Toll-like receptor (TLR), HO, leukocyte cascades and oxygen-free radicals (OFRs) (17,18). Understanding the mechanism of IR injury is crucial to reducing liver injury during liver surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a number of key factors associated with liver IR injury, such as Toll-like receptor (TLR), HO, leukocyte cascades and oxygen-free radicals (OFRs) (17,18). Understanding the mechanism of IR injury is crucial to reducing liver injury during liver surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Severe hepatic I/R injury causes not only liver failure but damage to other organs (14). Inflammatory events that occur during reperfusion lead to disruption of the integrity of the vascular endothelium and sinusoids, platelet aggregation, immunocyte activation (monocytes/macrophages, Kupffer cells, neutrophils), chemokine and cytokine secretion, and complement activation (32,45).…”
mentioning
confidence: 99%
“…2 Experimental reperfusion injury involves a cascade of events initiated by reactive oxygen intermediates (ROI) and ultimately resulting in graft invasion by polymorphonuclear cells and lymphocytes. Among the intermediate steps of this proinflammatory cascade, membrane derived compounds such as plateletactivating factor 3,4 ; cytokines like tumor necrosis factor (TNF), epithelial-activating neutrophil protein 78, and macrophage inflammatory protein 2 [5][6][7][8] ; and adhesion molecules including the CD18 family, intracellular adhesion molecule 1, and selectins [9][10][11][12] play a pivotal role in the recruitment and activation of neutrophils, the final mediators of injury. 9,13,14 Most of these events are thought to be mainly dependent on Kupffer cell activation.…”
mentioning
confidence: 99%